2018
DOI: 10.19111/bulletinofmre.438197
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Feldspar Raw Material Potential of Alkali Feldspar Granites and Alkali Feldspar Syenites Within Central Anatolia

Abstract: Alkali feldspar granites represent one of the major sources that provide raw materials for glass and ceramics industry because of their high feldspar and quartz contents. In addition, also alkali feldspar syenites have potential to become raw material due to their high feldspar and feldspathoid contents. For this reason, alkali feldspar granites within Ağaçören Intrusive Suite (AIS) (Kalebalta, Yıldırımlı, Çerkezuşağı, Çatalçeşme, İbrahimbeyli, Deliler, Ekecik, Sipahiler, Camili, Yaylak, Namlıkışla), Hacılı Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Alkali feldspar granites are granitoid rocks having the highest concentration of quartz and alkali feldspar. [23]. Both granite and granodiorite are intrusive plutonic rocks classified as granitic since they are quartz-rich.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali feldspar granites are granitoid rocks having the highest concentration of quartz and alkali feldspar. [23]. Both granite and granodiorite are intrusive plutonic rocks classified as granitic since they are quartz-rich.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that there are no substantial health hazards in the assessed region. In another study, Çıyrak [23] reported that radiation levels of granodiorites obtained from Bergama-Kozak were comparable with the world average and found to be safe for public and environment. The aim of this study is to determine the chemical, structural and ionization radiation shielding properties of the granitic rocks collected from the İzmir (Bergama-Kozak and Karaburun) and Kütahya (Simav) Provinces and evaluate their potential to be used as a radiation shielding material.…”
Section: Introductionmentioning
confidence: 85%
“…Thin sections were polished and coated with carbon to conduct electron micro-probe analysis (EPMA) Backscattered electron (BSE) images were taken, and EPMA analyzes were executed using JEOL brand JXA 8230 device under 20 kV voltage and 15 nA current at Ankara University YEBİM. The detailed procedure for performing the analysis has been reported in detail in Deniz and Kadıoğlu (2019). Microprobe analysis data are presented in Supplementary data (S1).…”
Section: Methodsmentioning
confidence: 99%
“…The recurrent observation of perthites in K-feldspars compensates for the low presence of plagioclases, particularly sodium plagioclase and thus the increasing of sodium content of Ina syenite as feldspathic flux raw material [17]. Quartz identified in some petrographic type also plays a key role in ceramic production at it increase stiffness, prevent deformation and reduce capillary cracking and thermal expansion of the product [71]. The fineness of the ferromagnesian matrix of these rocks has an impact on its structural nature which is also essential in that crush-ing and grinding could be done with reduced energy consumption [72].…”
Section: Potential Of Ina Syenite As a Source Of Feldspathic Fluxmentioning
confidence: 99%